Competitive Advantage of SMEs through Differentiation and Digitalization: A Case Study of Ash Scarf - Rita Anggraini Rahayu; Sudarmiatin Sudarmiatin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article discusses the concept of competitive advantage and its application in SMEs, with a case study on Ash Scarf, an SME in the hijab fashion industry. This study analyzes how Ash Scarf builds competitive advantage through differentiation and digitalization strategies. By referring to theories from Michael Porter and other experts, this research evaluates how Ash Scarf utilizes product uniqueness, customer service, and digital technology to compete in a competitive market. The research findings indicate that product differentiation and the effective use of digital platforms enable Ash Scarf to achieve a strong position in the market. This study also identifies the challenges SMEs face in implementing these strategies and provides recommendations for future development.